PERANAN PENDIDIKAN PRASEKOLAH UNTUK MENINGKATKAN KECERDASAN ANAK - Suratni Suratni (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2014)
This article is a review of literature on pre-school persepectives and intelligent quotient. Essentially, intelligent quotient is not a sole measurement of successful or failure of children in the future. In general, intelligent includes: intelligent quotient, emotional quotient, and spiritual intelligent. In the development that follows, Charles Spearman, Thurstone, and Gardner discovered theory on multiple intelligence. The theory identifies that intelligent covers seven dimentions, including: (1) linguistic, (2) music, (3) mathematics logic, (4) visual-spatial, (5) kinestetic-physic, (6) social-interpersonal, and (7) intra-personal. Multiple intelligent is now increasing and provides broader analysis on the interpretation of human behavior and successfulness.